Viaje al centro de la tierra - Verne, Jules, 1828-1905. (Madrid : Estudio Didactico)
A team of explorers makes an expedition into a crater which leads to the center of the earth and to incredible and horrifying discoveries.
Translation of: Voyage au centre de la terre.
Keywords: Explorers -- Juvenile fiction; Quests (Expeditions) -- Juvenile fiction; Geology -- Juvenile fiction; Exploradores -- Novela juvenil; Geologia -- Novela juvenil; Relatos de aventura; Earth -- Core -- Juvenile fiction; Tierra -- Estructura interna -- Novela juvenil; Adventure stories